METHODS OF STATE REGULATION OF THE MINING SECTOR OF THE ECONOMY OF UKRAINE - KINASH, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article presents modern methods of state regulation of the mining sector of the Ukrainian economy. It is established that the mining sector is a powerful sector of the Ukrainian economy, which creates the necessary level of energy security of the country. It is proposed to define the methods of state regulation of the mining industry as ways of favorable influence of the subjects on the activities of enterprises in the industry, which take into account the interests of man, society and the state. It was found that the state policy towards mining companies lies in the implementation of the Mining Law of Ukraine. The principles of state policy in this area and administrative bodies authorized to carry out state regulation are determined. The state policy on such natural resources as oil and gas is formed taking into account the specialized laws "On oil and gas", "On gas (methane) of coal deposits". State regulation of such companies is carried out through the establishment of general rules of their activities, the issuance of licenses, special permits for the use of oil and gas. Targeted development programs are a powerful tool for state regulation of the mining sector of the economy. The "National Program for the Development of the Mineral Resources Base of Ukraine for the Period up to 2030" is in force. An important tool for state regulation of the mining sector of Ukraine’s economy is to obtain subsoil use permits. It is investigated that 3118 permits are currently valid in Ukraine. These permits mainly concern the research and development of deposits and extraction of metals and non-metals, groundwater, hydrocarbons, coal and peat. As a result of the study, it was concluded that the choice of ways of state influence on the mining sector of Ukraine’s economy is determined by the goals, strategy, ways of development of Ukrainian society.